Neuropsychological performance in patients with subcortical stroke Perfil neuropsicológico em pacientes com lesões vasculares subcorticais - Silviane Pinheiro Campos de Andrade; Sônia Maria Dozzi Brucki; Orlando Francisco Amodeo Bueno; José Ibiapina Siqueira Neto (Arquivos de Neuro-Psiquiatria)
Vascular cognitive impairment (VCI) is characterized by cognitive compromise predominantly of executive dysfunction. OBJECTIVES: To assess cognitive functions in VCI, focusing on executive functions, to observe functional losses in relation to activities of daily living (ADLs) and to detect early symptoms prior to the onset of dementia. METHODS: We evaluated healthy subjects matched for gender, education and age to patients with diagnosis of subcortical vascular disease who had a stroke classified into three groups: 1) vascular lesions and no impairment; 2) vascular cognitive impairment with no dementia (VCIND); 3) vascular dementia (VaD). RESULTS AND DISCUSSION: The performance on neuropsychological tests differed among groups, worsening with increased impairment level. The probable VaD group demonstrated impaired performance in memory, processing speed and verbal production, while the VCIND group showed attention deficits. CONCLUSION: Impairment in executive functions and difficulties in ADLs allow us to differentiate levels of impairment in groups of subcortical vascular disease. O comprometimento cognitivo vascular (CCV) é caracterizado por comprometimento cognitivo predominantemente sob a forma de disfunção executiva. OBJETIVOS: Avaliar as funções cognitivas no CCV, enfocando as funções executivas, observar as perdas funcionais em relação às atividades cotidianas (AVDs) e detectar os primeiros sintomas antes do início da demência. MÉTODOS: Foram avaliados indivíduos controles saudáveis pareados por sexo, escolaridade e idade com pacientes com diagnóstico de doença vascular subcortical que sofreram derrame classificados em três grupos: 1) lesões vasculares sem déficit; 2) comprometimento cognitivo vascular sem demência (CCVSD); 3) demência vascular (DV). RESULTADOS E DISCUSSÃO: O desempenho em testes neuropsicológicos diferiu entre os grupos, sendo o desempenho tanto pior quanto maior o comprometimento. O grupo DV provável demonstrou desempenho prejudicado na memória, velocidade de processamento e produção verbal, enquanto o grupo CCVSD apresentou déficit de atenção. CONCLUSÃO: Prejuízos nas funções executivas e dificuldades em AVDs permitem diferenciar os níveis de comprometimento nos grupos de doença vascular subcortical.